On a Six-Parameter Generalized Burr XII Distribution - Olapade, A. K. (2014)
In this paper, we derive a probability density function that generalizes the Burr XII distribution. The cumulative distribution function and the n-th moment of the generalized distribution are obtained while the distribution of some order statistics of the distribution is established. A theorem that relates the new distribution to another statistical distribution is established.